PHYTOCHEMICAL SCREENING, ANTIBACTERIAL, AND ANTIOXIDANT ACTIVITIES OF CASSIA MONTANA HEYNE EX ROTH LEAF EXTRACTS - M, HEMALATHA; L, BHAKSHU; N, YASODAMMA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The leaf extracts of Cassia montana (Caesalpiniaceae) were being used for leucorrhea and rheumatic pains used by the certain tribal people in Andhra Pradesh. The present studies focused on the antibacterial, antioxidant activity of leaf extracts of C. montana which provide the scientific basis for its folklore applications in various ailments. Methods: Ethyl-alcohol and water extracts of C. montana (leaf) were screened for phytochemicals, antimicrobial activity and antioxidant activity using in vitro methods. The total phenolics were estimated using Folin–Ciocalteu reagent with reference to gallic acid, whereas the antioxidants of the extracts were quantified using ammonium molybdate reduction assay with reference to the ascorbic acid. The antibacterial activity was studied by disk-diffusion method and the radical scavenging assay by DPPH discoloration method with reference to ascorbic acid. Results: The leaf extracts were tested for antibacterial, antioxidants, and phytochemical screening and found the significant phytoconstituents as steroids, lignins, flavonoids, phenols, glycosides, tannins, cardiac glycosides, and reducing sugars in ethanol and aqueous extracts. The tested extracts exhibited significant antibacterial activity. It is also observed that ethanolic extracts are more effective with minimum inhibition concentrations values at 28 and 32 μg/disk against Bacillus subtilis and Staphylococcus aureus followed by Klebsiella pneumonia and Pseudomonas aeruginosa with 80 and 90 μg/disk. Total polyphenols quantified in alcohol and water extracts with reference to the gallic acid is 108 and 267 mg/g dry weight of leaf, respectively. Total antioxidants quantified in alcohol and water extracts with reference to the ascorbic acid is 70 and 85 mg/g dry weight of leaf, respectively. The tested extracts were exhibited strong effect on the discoloration of DPPH indicated the significant scavenging activity. Conclusion: The present study revealed that the tested extracts were exhibited significant anti-bacterial antioxidant activity along with the diversified phytochemicals. Hence, the leaf extracts of C. montana were having potential role in the treatment of ethno botanical health claims.